2011
DOI: 10.1590/s0001-37652011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Diet and nematode infection in Proceratoprhys boiei (Anura: Cycloramphidae) from two Atlantic rainforest remnants in Southeastern Brazil

Abstract: Proceratophrys boiei is an endemic cycloramphid anuran inhabiting the leaf litter of Atlantic rainforests in Southeastern Brazil. We analyzed the whole digestive tract of 38 individuals of Proceratophrys boiei collected in two Atlantic Rainforest areas in the state of Rio de Janeiro, Brazil, to study the diet composition and the helminth fauna associated with this species. The main food items in P. boiei's diet were Coleoptera, Orthoptera and Blattaria. Five nematode species were found: Aplectana delir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Ingestion of plant material is considered accidental in some cases, especially when its frequency of occurrence is very low (Klaion et al, 2011). However, in the case of P. ephippifer, ingestion of mineral and plant material may not be accidental as their frequency of occurrence was high.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of plant material is considered accidental in some cases, especially when its frequency of occurrence is very low (Klaion et al, 2011). However, in the case of P. ephippifer, ingestion of mineral and plant material may not be accidental as their frequency of occurrence was high.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Blattodea, Coleoptera, and Orthoptera are important prey for large leaf litter frogs, as they present large body sizes and mass, which provide an appropriate amount of food and energy (Boquimpani-Freitas et al 2002, Klaion et al 2011. Other arthropods such as Isopoda, Chilopoda and Araneae are also recognized as being an important volumetric contribution to the diet of medium-sized frogs (Van Sluys et al 2001, Dietl et al 2009).…”
Section: ) Feeding Habits Of Haddadus Binotatusmentioning
confidence: 99%
“…Similarly, Rhinella ornata (Bufonidae) consumed mainly Formicidae, Coleoptera and Orthoptera in EEEP and REGUA (Maia-Carneiro et al 2013), the same areas of the present study in the state of Rio de Janeiro. However, Proceratophrys boiei, a syntopic species with similar size to that of H. binotatus, had not only a similar diet, composed mainly by Coleoptera, Blattodea, and Orthoptera, but the prey shared similar importance in their diets (Giaretta et al 1998, Klaion et al 2011. The preference for different prey types, in leaf litter frog assemblages, may be evolved as a mechanism to allow the coexistence of species with similar food and habitat requirements, or simply may reflect the more frequent encountered prey.…”
Section: ) Feeding Habits Of Haddadus Binotatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, there are isolated occurrence records and ecological observations on some species of frogs (Weber et al 2007, Silva-Soares et al 2008, Klaion et al 2011, MaiaCarneiro et al 2012a, b, 2013, Salles et al 2012), lizards (Goyannes-Araú jo et al 2009, Maia et al 2011, Almeida-Gomes et al 2012, and snakes (Alves et al 2005, Silveira et al 2010). Here, we present the list of amphibian and reptile species based on records obtained during nearly ten years of surveys at REGUA and its surroundings.…”
Section: Introductionmentioning
confidence: 99%